(untitled) (European Journal of Pure and Applied Mathematics, 2025)
Several recent papers gave numerical radius inequalities for sums and products of operators which are defined on a complex separable Hilbert space H. In this paper, we prove a numerical radius inequality which generalizes and refines a recent inequality proved by Kittaneh.